Phases: An essay on cyclicity in syntax - Abels, Klaus (Linguistische Arbeiten, 2012)
The minimalist notion of a phase has often been investigated with a view to the interfaces between syntax and the syntax-external systems. The current volume provides a syntax-internal perspective on phases. If the phase is fundamental to the theory, it should provide the foundation for a unifying treatment of different syntactic phenomena. This book concentrates on displacement and claims that the concept of the phase allows a unifying treatment of successive cyclicity, pied-piping, secondary movement, partial movement, and stranding across many languages. Klaus Abels, UCL London, UK.